Investigação da participação do HMGB1 na ativação dos receptores RAGE e TLR4 em células da glia espinais durante a dor neuropática induzida por Paclitaxel - Moraes, Thamyris Reis (2022)
Chemotherapy-induced neuropathic pain is the main adverse effect of chemotherapeutic drugs and is related to a decrease in the quality of life of cancer patients, which can even lead to treatment discontinuation. At the spinal level, the modulation of this type of pain involves not only neurons but also glial cells that, when activated, increase the expression of receptors and intracellular signaling, resulting in the release of pro-inflammatory mediators. The high- mobility box-1 protein (HMGB1) is released during neuropathic pain and its role in pain development consists of its interaction with receptors activating signaling pathways. Therefore, the present study investigated the role of HMGB1 in glial cells, RAGE, and TLR4 receptors, and MAPK p38 and NFkB signaling, as well as the involvement of these pathways in paclitaxel-induced neuropathic pain. For this, C57BL/6 and C57BL/6 TLR4 (-/-) male mice weighing between 20 and 25g were used. The von Frey filaments apparatus was used to assess the nociceptive threshold. For the induction of neuropathic pain, the chemotherapy agent paclitaxel was used, which was administered every other day for 6 days. Recombinant HMGB1 protein was administered i.t. to investigate its effect on the nociceptive threshold. The participation of RAGE and TLR4 receptors was investigated using the respective antagonists FPS-ZM1 and LPS-RS administered intrathecally. The participation of microglia, astrocytes, MAPK p38 and NFkB was evaluated using the inhibitors minocycline, fluorocitrate, SML0540, and PDTC, respectively, also by i.t. The Western blot assay was performed to assess the protein levels of HMGB1, RAGE, TLR4, Iba1, and GFAP and the Elisa assay to assess the levels of HMGB1, TNF-α, and IL1-β. The results indicate the participation of RAGE and TLR4 receptors, microglia, astrocytes, and MAPK p38 and NFkB signaling in both HMGB1-induced nociception and paclitaxel-induced neuropathic pain. It was also observed an increase in HMGB1 protein levels in the genesis of neuropathic pain, and the involvement of TLR4 receptors in microglial activation. Blockade of RAGE and TLR4 receptors led to a decrease in pro-inflammatory cytokines. These results indicate that HMGB1 released in the initial paclitaxel treatment activates RAGE and TLR4 receptors in microglia, increasing levels of pro-inflammatory cytokines and contributing to neuropathic pain.